In-vessel co-composting of biosolid: Focusing on mitigation of greenhouse gases emissions and nutrients conservation. (December 2018) - Awasthi, Mukesh Kumar; Wang, Quan; Chen, Hongyu; Wang, Meijing; Awasthi, Sanjeev Kumar; Ren, Xiuna; Cai, Hanzhen; Li, Ronghua; Zhang, Zengqiang
Abstract: In this paper study the feasibility of Calcium-bentonite (Ca-B) combined with biochar (B) as an effective amendment for the co-composting of dewatered fresh sewage sludge (DFSS) mixed with wheat straw (WS), focusing on mitigation of greenhouse gases (GHG) emission and nutrients loss. The 12%B mixed with three different concentration of Ca-B (2%, 4% and 10%) was supplemented into 1:1 ratio mixture of DFSS and WS (dry weight basis), while compared with a 12%B alone and control or without any amended treatments. This experiment lasted for 42 days in a 130-L reactor. The CH4 and N2 O emission profiles were clearly indicated that 12%B alone and 12%B + Ca-B addition effectively buffered the composting mass and enhanced the rate of organic matter mineralization as compared to control treatment. Among the all treatments, minimum TOC (16.83%), TKN (0.38%) and dry matter (29.73%) losses were observed in 12%B+4%Ca-B applied treatment; and also improved compost quality compared to control. Furthermore, 12%B+4%Ca-B amendment was beneficial to the efficient organic matter degradation and low quantity of total GHG production from the feedstock without inhibition to composting compared with control treatment. Therefore, 12%B+4%Ca-B amendment is a promising ecofriendly solution for DFSS co-composting because it contributes to reduce the total GHG emission and produced matured compost with sound management of DFSS in China.